PERAN ETIKA AKUNTAN DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD - Hana Nurafifah; Oktavia Lhaksmi Pramudyastuti (Bajang Institute, 2022)
The purpose of this study is to find out the ethical role of accountants and good corporate governance in fraud prevention. The research uses qualitative research methods and is based on theoretical studies as well as previous research findings. Previous research has shown that weak implementation of good corporate governance can lead to fraud. An accountant must comply with ethics or code of ethics in carrying out his professional duties so as to prevent fraud/ fraud. This research data is collected, examined and concluded. Fraud or fraud occurs in organizations or companies either private or government where this fraud occurs because of various factors that encourage it. Fraud also occurs in Indonesia not only abroad with various factors behind it. In preventing fraud, an understanding of the structure, mechanisms, principles and functions of corporate governance is needed. So that good company management will prevent and reduce the occurrence of fraud / fraud. As an accountant, it is also necessary to comply with existing ethical rules in accordance with the code of ethics so that accountants can uphold their responsibilities and professionalism in carrying out their duties and include programs in fraud prevention.